Σχεδιασμός θεμελίωσης διώροφης οικοδομής, σε αργιλώδες έδαφος χαμηλής διατμητικής αντοχής - Καραγιάννης, Παναγιώτης (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This current diplomatic project aims to the design of a shallow foundation of a two story residence, that is based on clay ground. The diplomatic project is thus presented: Chapter 1. There is a precise determination of the problem. Specifically, the characteristics of the ground, the floor plan of the residence and the effect suspensions of the design of the pillars are presented. Chapter 2. Includes of the calculation of the footings as well as the total of the active surfaces. At chapter 3, the bearing capacity of the ground is being calculated and based on that, the dimensioning of the footings is being made. At chapter 4, the subsidence (immidiate and consolidation) of the footings that have been previously dimensioned, are defined and later checked based on the permissible limits of subsidence. Chapter 5, if it is required for the present building, a combined footing is designed. Still, a description of the procedure of the connection of the two footings with a Cantilever Strap of the connecting beams is being suggested. At chapter 6, design of spread footing with the jWinkler program.
Keywords: Shallow foundation; Bearing capacity; Settlement; Combine footing